2018
DOI: 10.1007/s40843-017-9191-5
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-templated synthesis of sandwich-like porous carbon nanosheets for efficient oxygen reduction reaction in both alkaline and acidic media

Abstract: Developing low-cost, high-performance electrocatalysts for the oxygen reduction reaction (ORR) is crucial for implementation of fuel cells and metal-air batteries into practical applications. Graphene-based catalysts have been extensively investigated for ORR in alkaline electrolytes. However, their performance in acidic electrolytes still requires further improvement compared to the Pt/C catalyst. Here we report a self-templating approach to prepare graphene-based sandwich-like porous carbon nanosheets for ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…The O 1s peak can be deconvoluted into three peaks of the O−C (O 1 ) at the BE of 531.5 eV, the O=C (O 2 ) at 532.6 eV and the O−C=O at 533.8 eV (C−O; O 3 ), respectively. As shown in Figure S2 (a–d), the S 2p peak can be fitted into three peaks of the S 1 and S 2 for −C−S−C− at the BE of 163.9 and 165.0 eV, and the S 3 for −C−SO 2 −C− at the BE of 168.0 eV . Previous studies have shown that the −C−S−C− group may increase the ORR activity .…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The O 1s peak can be deconvoluted into three peaks of the O−C (O 1 ) at the BE of 531.5 eV, the O=C (O 2 ) at 532.6 eV and the O−C=O at 533.8 eV (C−O; O 3 ), respectively. As shown in Figure S2 (a–d), the S 2p peak can be fitted into three peaks of the S 1 and S 2 for −C−S−C− at the BE of 163.9 and 165.0 eV, and the S 3 for −C−SO 2 −C− at the BE of 168.0 eV . Previous studies have shown that the −C−S−C− group may increase the ORR activity .…”
Section: Resultsmentioning
confidence: 71%
“…As shown in Figure S2 (a–d), the S 2p peak can be fitted into three peaks of the S 1 and S 2 for −C−S−C− at the BE of 163.9 and 165.0 eV, and the S 3 for −C−SO 2 −C− at the BE of 168.0 eV . Previous studies have shown that the −C−S−C− group may increase the ORR activity . The contents of S element in PPy/C‐500, PPy/C‐700, PPy/C‐900 and PPy/C‐1050 are respectively 0.20, 0.16, 0.21 and 0.17 at%, which are rather low and change little with the annealing temperature.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Oxygen reduction reaction (ORR) catalysts for the cathodic reaction of DMFCs have been extensively investigated to replace platinum-containing groups, with the aim of enhancing the catalytic activity of ORR while reducing the cost [4,5]. A number of alternative ORR catalysts including non-precious metal (NPM), metal composites, and metal-free composites have been recently considered as potential substitutes for platinum-containing groups catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-based nanoparticles (NPs) were often generated by an annealing process [19][20][21][22][23], and significant progress in metal-based NPs encapsulated within heteroatomdoped carbon catalysts for ORR has been reported [24]. During the annealing process, metal or other heteroatoms were doped into carbon matrix, and metal-based NPs were encapsulated by heteroatom-doped carbon layers.…”
Section: Introductionmentioning
confidence: 99%